2023
DOI: 10.1093/jrr/rrad037
|View full text |Cite
|
Sign up to set email alerts
|

Relative biological effectiveness for epithermal neutron beam contaminated with fast neutrons in the linear accelerator-based boron neutron capture therapy system coupled to a solid-state lithium target

Abstract: This study aimed to quantify the relative biological effectiveness (RBE) for epithermal neutron beam contaminated with fast neutrons in the accelerator-based boron neutron capture therapy (BNCT) system coupled to a solid-state lithium target. The experiments were performed in National Cancer Center Hospital (NCCH), Tokyo, Japan. Neutron irradiation with the system provided by Cancer Intelligence Care Systems (CICS), Inc. was performed. X-ray irradiation, which was assigned as the reference group, was also perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The energy and intensity of neutrons are adjusted to be optimal for BNCT in the accelerator-based BNCT. Thus, previous reports indicated that RBE value of neutron beam in the accelerator-based BNCT was lower than that in the reactor-based BNCT (13,17,18). Furthermore, the accelerator-based BNCT also expects shorter irradiation time.…”
Section: Discussionmentioning
confidence: 95%
“…The energy and intensity of neutrons are adjusted to be optimal for BNCT in the accelerator-based BNCT. Thus, previous reports indicated that RBE value of neutron beam in the accelerator-based BNCT was lower than that in the reactor-based BNCT (13,17,18). Furthermore, the accelerator-based BNCT also expects shorter irradiation time.…”
Section: Discussionmentioning
confidence: 95%